2018
DOI: 10.1080/1828051x.2017.1420430
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of differences in prion protein gene (PRNP) polymorphisms between Algerian and Southern Italy's goats

Abstract: Goats are adapted to live in harsh areas of the world ensuring minimum levels of milk and meat production without much economic input. Scrapie is a fatal prion disease of small ruminants detected in different countries worldwide. Polymorphisms in the prion protein gene (PRNP) modify the degree of susceptibility/resistance to scrapie. PRNP polymorphisms were analysed in the four main Algerian goat breeds (Naine de Kabylie, Arbia, Mozabite, Mekatia), and in two native breeds of South Italy (Aspromontana from Cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 31 publications
(49 reference statements)
1
19
1
Order By: Relevance
“…Substitution with a different variant having different physicochemical properties might influence the conformational plasticity of prion protein and my further could tempt the emergence of new scrapie disease form.Similar to previous studies, additional amino acid polymorphic sites i.e. G126A, G126A(heterozygous), G127G, G127V(heterozygous), G127A(heterozygous), S138S, I142IT, N146S, N146S(heterozygous), R231R, and L237L were identified[3][4][5][6]. In the present study, the variant at position 127 was in particular highly polymorphic.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Substitution with a different variant having different physicochemical properties might influence the conformational plasticity of prion protein and my further could tempt the emergence of new scrapie disease form.Similar to previous studies, additional amino acid polymorphic sites i.e. G126A, G126A(heterozygous), G127G, G127V(heterozygous), G127A(heterozygous), S138S, I142IT, N146S, N146S(heterozygous), R231R, and L237L were identified[3][4][5][6]. In the present study, the variant at position 127 was in particular highly polymorphic.…”
supporting
confidence: 90%
“…An earlier study linked genotypes such as AC 151 RQ to prolonged incubation period after scrapie exposure [10]. Together with that, several studies reported polymorphisms such as G126A, G126G, G127G, G127V, G127A, and S138S [3][4][5][6] in sheep prion protein with or without direct effect to susceptibility to scrapie.…”
mentioning
confidence: 84%
“…R154H variant was detected at a low frequency in Afar(present study), Western highland, Long Eared Somali, and Aegean region goat breeds 12,26 . R154H variant in the Algerian breed has been reported in 15-26% of the study population 9 . The variant T193I was first reported in a recent study by Vitale M. et al, 2019 at a frequency similar to the current observation 12 .…”
Section: Discussionmentioning
confidence: 85%
“…The presence of p.(Asn146Ser) in Halep (Damascus), Ethiopian and Tanzanian native goats suggests that the allele was naturally selected in the Middle East first, and spread through the central Sahara and Ethiopia later [35, 36] and subsequently into southern parts of the African continent through a different migration route compared to the main Mediterranean and North African routes. As in the Sicilian Damascus breed, p.(Asn146Ser) has not been detected so far in Algerian, Tunisian and Moroccan goats [37, 38]…”
Section: Discussionmentioning
confidence: 99%